2015
DOI: 10.1080/19420862.2015.1085145
|View full text |Cite
|
Sign up to set email alerts
|

Rapid quantitative analysis of monoclonal antibody heavy and light chain charge heterogeneity

Abstract: To cite this article: Ram P Vanam, Michael A Schneider & Michael S Marlow (2015) Rapid quantitative analysis of monoclonal antibody heavy and light chain charge heterogeneity, mAbs, 7:6, 1118-1127, DOI: 10.1080DOI: 10. /19420862.2015 An alternative method to traditional 2-dimensional gel electrophoresis (2D-PAGE) and its application in characterizing the inherent charge heterogeneity of chromatographically isolated monoclonal antibody heavy and light chains is described. This method, referred to as ChromiCE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…IEF is one of the most commonly used techniques for resolving charge variants (Dada, Jaya, Valliere‐Douglass, & Salas‐Solano, ; Hazeltine et al, ; Horvath, Mun, & Laird, ; Hosken, Li, Mullappally, Co, & Zhang, ; Kaschak et al, ; Rouiller et al, ; Vanam, Schneider, & Marlow, ; Yang, Minkler, Kshirsagar, Ryll, & Huang, ; Yoon, Song, & Lee, ). IEF techniques separate molecules based on the molecules' pI and overall charge, and the detection is achieved by UV absorption at 280 nm.…”
Section: Principles Of Charge Variants Analyticsmentioning
confidence: 99%
“…IEF is one of the most commonly used techniques for resolving charge variants (Dada, Jaya, Valliere‐Douglass, & Salas‐Solano, ; Hazeltine et al, ; Horvath, Mun, & Laird, ; Hosken, Li, Mullappally, Co, & Zhang, ; Kaschak et al, ; Rouiller et al, ; Vanam, Schneider, & Marlow, ; Yang, Minkler, Kshirsagar, Ryll, & Huang, ; Yoon, Song, & Lee, ). IEF techniques separate molecules based on the molecules' pI and overall charge, and the detection is achieved by UV absorption at 280 nm.…”
Section: Principles Of Charge Variants Analyticsmentioning
confidence: 99%
“…RSD values for isoelectric points and migration times were below 0.2% and 4%, respectively. Vanam et al showed that the charge heterogeneity of chromatographically isolated antibody fragments (heavy and light chains) can be resolved using analytical SEC followed by icIEF, with a significant increase in throughput compared to 2D-PAGE . Shimura et al used ciEF to determine the asparagine deamidation rates of a mouse IgG1 Fab .…”
Section: Electrophoretic Approachesmentioning
confidence: 99%
“…Vanam et al showed that the charge heterogeneity of chromatographically isolated antibody fragments (heavy and light chains) can be resolved using analytical SEC followed by icIEF, with a significant increase in throughput compared to 2D-PAGE. 150 Shimura et al used ciEF to determine the asparagine deamidation rates of a mouse IgG1 Fab. 151 Five asparagine residues were mutated one by one through sitedirected mutagenesis, and the deamidation rates of the original Fab and the mutants were determined using ciEF.…”
Section: ■ Electrophoretic Approachesmentioning
confidence: 99%
“…Capillary isoelectric focusing (cIEF) and cation exchange chromatography (CEX) are commonly used for the characterization of protein charge variants. [4][5][6][7] Using a pH gradient and electric field, cIEF separates charge variants based on the intrinsic charge of the molecule. In CEX, either salt or pH gradients have been successfully applied for the characterization of charge variants.…”
Section: Introductionmentioning
confidence: 99%